Lipid peroxidation and antioxidant enzymes of blood in patients with chronic nonhealing stomach ulcer treated with actovegin and lipostabil - Gr SADİKOVA and As KOMARİN and Vn GORBUNOV (Turkish Journal of Gastroenterology, 2019)
-